Experimental Study on Influence of Height of Full-Width Plate Weirs on Flow Behavior, Discharge, and Energy Dissipation - Ali Mahdian Khalili; Hossein Sohrabzadeh Anzani; Mehdi Hamidi; Sameh Ahmed Kantoush (Hydrology, 2025)
The role of weirs in flow regulation in water resources infrastructure and flood control is well known. In the meantime, the study of full-width plate weirs (FWPW), due to their wide application and lacking findings, is of great importance. In this study, experimental models were conducted at Babol Noshirvani University of Technology to investigate flow passing through FWPWs with five different heights (p = 0.07, 0.09, 0.11, and 0.15 m) under eight discharge conditions (Q = 1.4 to 6.3 L/s). The experiments were carried out in a flume measuring 4 m in length, 0.6 m in width, and 0.2 m in height. The discharges were measured with a calibrated flowmeter, and the water depths upstream of the weir (h) and the tailwater depths (h1) were measured with a point gauge with an accuracy of 0.1 mm. For each test, the discharge coefficient (Cd), relative residual energy (E1/E0), and relative energy dissipation ((E0 − E1)/E0) were computed. The proposed equation for calculating discharge achieved good accuracy with RMSE = 0.0002, MAE=0.0002, and R2 = 0.997. Results show a reducing trend of Cd by increasing h/P, which is compatible with previous results. It was observed that at a constant discharge, relative residual energy reduces by an average of 47% by increasing weir height, and at a constant P, increasing flow discharge increases it a little. A novel accurate equation for relative energy dissipation in FWPW was proposed based on h/P that provided specific constant coefficients for each p value.